Design, Fabrication And Characterization Of Fr4-Based Dna Label Free Sensor Integrated With Pocket-Sized Readout Circuitry - Hamzah, Irni Hamiza (2013)
Silicon, glass and ceramic are commonly base substrates used in SU8 film fabrication and DNA biosensor. All these substrates are biocompatible, expensive, hard and brittle, difficult for drilling and dicing, requires expensive equipments and complex methodology of fabrication. Microcracks are often found on SU8 film due to the large gap of thermal expansion coefficient (TEC) between silicon/glass and SU8. In addition, the use of bulky equipments and accessories that must be interfaced with hardware and software through a central processing unit (CPU) limits the portability of the whole biosensor system. Hence, the aim of this work is to investigate on the suitability of polymethylmethacrylate (PMMA) to be used as a base substrate for SU8 film fabrication and the application of a non-biocompatible material, flame retardant 4 (FR4) as a base substrate for a label free DNA biosensor. A portable and handy readout circuitry with double-sided pocket-sized of PCB for DNA detection through current measurement cyclic voltammetry (CV) method has been developed and integrated with the FR4-based fabricated sensor. The Au is fabricated throughout all conducting tracks on the FR4 and the characterization of the fabricated FR4-based sensor to perform CV reversible process is confirmed by a series of analysis. The thiol group at the 3’-end of ssDNA is used to link the DNA with the Au surface and act as probe DNAs. Two types of target DNAs which consist of complementary nucleobase sequence and noncomplementary nucleobase sequence are used to investigate on the hybridization mechanism with the probe DNAs.